Towards new experiences for international cooperation: A multidisciplinary ICT and business international project - Seruca, Isabel (2019)
A new experience in International Cooperation was launched by Fontys Hogeschool ICT, Netherlands in the form of an Interdisciplinary ICT and Business International Project, involving Bachelor third-year students and teachers from several Higher Education Institutions (HEI) partners. The main project objectives are International cooperation and awareness, demonstrating entrepreneurship behavior and an interdisciplinary vision. This kind of International Cooperation overcomes the problems often found in other mobility actions’ applications under the Erasmus+ Programme framework, where high quality standards, rigid schemes of functioning and other selection criteria may hamper the possibilities for recognition and funding. This paper describes the development and implementation of an Interdisciplinary ICT and Business International project, supervised by the authors, aiming to develop innovative Business IT solutions under the central topic “Obesity & healthy lifestyle”. The project was developed both in loco and in a remote way, where the initial kick-off was made at Fontys ICT and the closure at the second HEI partner, Portucalense University and involved students from both HEIs with ICT and business backgrounds. The work of the four project student teams is described, the methodology and outcomes assessed and lessons learnt are highlighted. The results of the assessment, conducted to measure both learning outcomes and student satisfaction with and opinions of the project, are included along with a summary of the experience gained by students and teachers while taking part in the project. The paper aims to share implementation and assessment of such a project as an opportunity for HEI’s to acknowledge new ways of international cooperation, for entrepreneurship educators to learn from others' experiences, and to contribute to the entrepreneurship education literature.